Model Manajemen Produksi Film Dokumenter Bulu Mata Karya Tonny Trimarsanto - Khalda Ahmad Muafa; Fajar Junaedi (Universitas Ahmad Dahlan, 2020)
This research discusses about production management of a documentary film Bulu Mata which was produced in collaboration between an organization called Suara Kita and Rumah Dokumenter to raised the issues of transgender. This research aim to find out how the production management model used in the pre-production, production, and post-production during the filmmaking process. This research used a positivistic approach with case study method. The research data obtained from in-depth interview, documentation, and literature. The result showed in the pre-production step are planning ideas, research, storytelling approach, and production design. Then in the production step, the production crew prepared tool, briefing with film subjects, and ready to takes the audio visual. And the finally, the post-production step are editing, discussion, preview, and correction until the film was finished. So, the conclusion of this research want to know the production management model used during the filmmaking process.